Autocorrelation-based adaptation rule for feedback equalization in Wideband Full-Duplex Amplify-and-Forward MIMO relays - Emilio Antonio-Rodríguez; R. López-Valcarce; Taneli Riihonen; Stefan Werner; Risto Wichman (Int. Conf. Acoust., Speech, Signal Process. (ICASSP), 2013)
Simultaneous reception and transmission in the same frequency, so-called full-duplex operation, causes an infinite feedback loop in an amplify-and-forward relay. The unwanted echoes may result in oscillation at the relay, making it unstable, and distorting the spectrum. This paper presents an adaptive MIMO filtering method for full-duplex amplify-and-forward relays that aims at solving the joint problem of self-interference mitigation and equalization of the source-relay channel. The scheme exploits knowledge of the autocorrelation of the transmitted signal as the only side information while allowing the relay, in the best case, to implement precoding as if there was not any self-interference or frequency selectivity in the source-relay channel. Finally, the proposed adaptation algorithm is investigated by determining its stationary points and by performing simulations in a MIMO-OFDM framework.
Keywords: adaptive signal processing; dynacs; full duplex